Racial identities and prison in the Western Cape : the case of the "Coloured" community. - (:unkn) unknown (My University, 2017)
My research focuses on race and incarceration in South Africa. People in the "Coloured"community are overrepresented in incarceration statistics, both on the national and onthe regional level. With the help of inmates' life stories gathered at various correctionalcentres in the Western Cape, my thesis seeks to make sense of this phenomenon.
Keywords: African Research